A study of two variables Legendre polynomials - Khan, Mumtaz Ahmad (2010)
The present paper deals with a study of a two variable polynomial Pn(x) analogues to the Legendre polynomial Pn(x). The paper contains differential recurrence relations, a partial differential equation, double generating functions, double and triple hypergeometric forms, a special property and a bilinear double generating function for the newly defined polynomials Pn,k(x, y).